A CASE OF TORNWALDT'S DISEASE - Sonoda, Fumiko (JIBI INKOKA TEMBO, 1986)
Bursa pharyngea is an embryological structure in the nasopharynx and occasionally cause a condition named Tornwaldt's disease. The disease is due to the persistance of bursa pharyngea, which lies dormant in most instances until trauma such as adenoidectomy occurs and the orifice of it is occluded. The persistance of bursa pharyngea is reported to be observed over 40% of human embryo and under 4% of adults. But reports of Tornwaldt's disease are rare and there have been only 9 reports in Japan until today. The authors have experienced a case of a man, aged 44, who complained of hearing loss and stuffed feeling of his right ear. His audiogram showed about 40 db conductive hearing loss and tymoanogram was C type. A large cyst was seen in his nasopharynx and it was remored with remarkable improvement of the symptoms.